Exploring the Therapy of Islamic Psychology, Mindfulness and Gratitude Emotion in Harmonising Islamophobic Behaviour - Jamil, Jamaliah; Ali, Idris (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
Technology and social media have become an indispensable part of our lives, affecting our households in various ways. Unfortunately, this has resulted in significant psychological and emotional disturbances. One of the negative outcomes of this is the prevalent Islamophobic behaviour towards Muslims, regardless of their citizenship. This behaviour is further amplified by the rapid spread of such sentiments on social media platforms. This article seeks to delve into the secular and Islamic perspectives on the history and approach of human psychology, examining the overwhelmed phenomenon of Islamophobia. It begins by defining the psychological concept from both Western-secular and Islamic perspectives, comparing the two ideas with past historical events. The final part of the article explores how the artificial intelligence era has impacted both Western and Eastern populations, highlighting the psychological impact of Islamophobia. The article suggests that psychologists should undertake a comprehensive study to improve psychological therapy, such as Religious-Integrative Cognitive-Behavioral therapy. This form of therapy incorporates prayer, mindfulness, and gratitude scales to help reduce the western service provider violence behaviour caused by Islamophobia mental-illness. This study provides a unique intellectual discourse on Islamophobia’s psychological treatment, which is currently underrepresented in mainstream academic literature.